2013
DOI: 10.1371/annotation/2296467f-c10a-4677-8520-490a614ce355
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Hibernating Little Brown Myotis (Myotis lucifugus) Show Variable Immunological Responses to White-Nose Syndrome

Abstract: White-nose syndrome (WNS) is an emerging infectious disease devastating hibernating North American bat populations that is caused by the psychrophilic fungus Geomyces destructans. Previous histopathological analysis demonstrated little evidence of inflammatory responses in infected bats, however few studies have compared other aspects of immune function between WNS-affected and unaffected bats. We collected bats from confirmed WNS-affected and unaffected sites during the winter of 2008-2009 and compared estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Alkanes and methylated alkanes also have been associated with oxidative stress and lipid peroxidation [ 54 , 55 , 56 ]. Moore et al [ 57 ] provided evidence that oxidative stress was a significant factor contributing to WNS-associated mortality. Lawal et al [ 52 ] found several alkanes including decane, hexane, octane and cyclohexane that were elevated when epithelial cells were exposed to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkanes and methylated alkanes also have been associated with oxidative stress and lipid peroxidation [ 54 , 55 , 56 ]. Moore et al [ 57 ] provided evidence that oxidative stress was a significant factor contributing to WNS-associated mortality. Lawal et al [ 52 ] found several alkanes including decane, hexane, octane and cyclohexane that were elevated when epithelial cells were exposed to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The CA-biomarkers do not appear to be related to physiological activities associated with vigorous physical activities (such as flying), but are more associated with sedentary awake activities such as cleaning or grooming off activities which are conscious activities more commonly practiced by active field bats or bats that have recently entered a cave (and have not yet initiated torpor), and less common in torpid cave bats that engage in grooming activities only for brief intermittent periods during infrequent prolonged arousals. The release of CA-biomarkers in cave bats also may possibly be correlated with activation of major histocompatibility complex (MHC) immune responses when bats are awake, involving cytokine production, that have been indicated as adaptive immunity to WNS in certain European bat species developing long-term resistance, but may not yet be fully or effectively operating in North American bat species due to only recent occurrence of this disease [ 57 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%